MODEL OF A TERMINAL NETWORK DEVICE BASED ON A SINGLE-CHIP MICROCONTROLLER AND ETHERNET INTERFACE: MODEL OF A TERMINAL NETWORK DEVICE BASED ON A SINGLE-CHIP MICROCONTROLLER AND ETHERNET INTERFACE - Denev, Daniel; Tsankov, Tsvetoslav (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Model of a terminal network device based on a single-chip microcontroller and Ethernet interface: In the present work, a training model of a terminal network device based on a single-chip microcontroller and Ethernet interface is built, allowing the implementation of various functional tasks: ⎯ reading of digital and analog sensors ⎯ relay output control ⎯ visualization of information with digital – alphanumeric display